ANALISA SUATU PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KELURAHAN PANGGUNGHARJO KAB. BANTUL DIY - Ikhsan, Foster; Hasanah, Muqimatul (Bussman Journal : Indonesian Journal of Business and Management, 2022)
The research sample was 50 respondents taken from employees of the Pangguharjo Village, Sleman Yogyakarta. The research results conclude that there is a significant effect between mPrior work motivation has no effect because the way it works is monotonous so it doesn’t improve work performance. Work motivation during a pandemic affects employee performance because it has a change in work patterns on employee performance in the Panggungharjo Village, Kab. DIY Bantul. The work environment before Covid-19 had a significant effect on employee performance because before the pandemic the work system was carried out offline and it affected employee performance. Unlike the case during Covid19, the work environment had no effect because the work system changed to online so that the work environment that was obtained offline was not obtained by an online system so this did not affect employee performance